Peran Short Chain Fatty Acids (SCFAs) Terhadap Kejadian Hipertensi - Agus Sulaeman; Puput Novriana; Marita Kaniawati (Jurnal Ilmiah Farmasi, 2022)
Background: Hypertension is a persistently elevated arterial blood pressure called the silent killer because sufferers often do not show signs and symptoms. Low Short Chain Fatty Acids (SCFA) is a risk factor for hypertension. Therefore, many efforts have been made in overcoming hypertension through the role of SCFA. Objective: This review article was conducted to see the SCFA mechanism against the incidence of hypertension so that it is hoped that we can find medicinal plants that can prevent and treat hypertension.Method: This article is compiled based on a review of several works of literature related to the role of SCFA in hypertension from articles published in the electronic database.Results: The SCFA mechanism is involved in lowering blood pressure through G-protein coupled receptors (GPCRs). Acetate binding to GPR43 causes hyperpolarization of the colonic epithelium, propionate activates GPR41 signals located in the vascular endothelium and butyrate binds to GPR109a and exerts anti-inflammatory effects. It was also found that giving baicalin and olive oil was shown to increase SCFA-producing bacteria.Conclusion: The role of SCFA in the development of hypertension occurs through the mechanism of diffusion and transport of solutes from SCFA which then activates GPCRs including GPR43, GPR41, and GPR109a so that they have a vasodilating effect by reducing inflammation, improving intestinal permeability, decreasing sympathetic nerve activity, and increasing Treg cells. Keywords: gut microbiota; SCFA; hypertension Intisari Latar belakang: Hipertensi adalah tekanan darah arteri yang meningkat secara persisten disebut juga silent killer karena penderita sering tidak menampakkan tanda dan gejala. Rendahnya Short Chain Fatty Acids (SCFA) menjadi faktor risiko dari hipertensi. Oleh karena itu, telah banyak upaya yang dilakukan dalam mengatasi hipertensi melalui peran SCFA.Tujuan: Review artikel ini dilakukan untuk melihat mekanisme SCFA terhadap kejadian hipertensi sehingga diharapkan dapat mencari tanaman obat yang dapat mencegah dan mengobati hipertensi.Metode: Artikel ini disusun berdasarkan review beberapa literatur yang terkait peran SCFA dalam hipertensi dari artikel yang diterbitkan di electronic database.Hasil: Mekanisme SCFA yang terlibat dalam penurunan tekanan darah melalui G-protein coupled receptors (GPCRs). Asetat mengikat GPR43 menyebabkan hiperpolarisasi epitel kolon, propionat mengaktifkan sinyal GPR41 yang terletak di endotel vaskuler dan butirat mengikat GPR109a memberikan efek anti-inflamasi. Kesimpulan: Peran SCFA dalam perkembangan hipertensi terjadi melalui mekanisme adanya difusi dan transport zat terlarut dari SCFA yang kemudian mengaktivasi GPCR termasuk GPR43, GPR41 dan GPR109a sehingga memberikan efek vasodilatasi dengan menurunkan inflamasi, memperbaiki permeabilitas usus, menurunkan aktivitas saraf simpatis dan meningkatkan sel Treg.Kata kunci: mikrobiota usus; SCFA; hipertensi